Новые находки антропоморфных бронзовых фигурок уродцев - Гриб, В.К.; Давыденко, В.В. (Степи Европы в эпоху средневековья, 2012)
По сюжетам и технике статуэтки этого рода составляют совершенно обособленное явление, которое, однако, нельзя усвоить одной определенной местности или народу, в виду того, что места нахождения их чрезвычайно разбросаны друг от друга”. Так писал в 1909 г русский археолог А.А.Спицын в статье, которая, собственно, и положила начало научному изучению бронзовых антропоморфных фигурок, получивших в специальной археологической литературе название “уродцы” . At present over 60 copies of anthropomorphous bronze figurines called “lususes” in the archaeological literature have been found. In this paper the authors describe six new figurines found on the Northern and Eastern Azov Sea Littoral, in the medium reaches of the Severskii Donets river, and in Western Siberia. Three of these objects (i.e. those found at Pristino, the Kuban river and in Western Siberia) are unique in their structural features. For the first time in the history of studying this category of objects an attempt to graphically reconstruct the apt applicability of the figurines in family or tribal ceremonies of the early Turkic tribes nomadising throughout the vast territory of the Eurasian steppes in the 8th-11th centuries has been made.